The changing face of the Metis nation - Gibbs, Ellen Ann; University of Lethbridge. Faculty of Arts and Science (Lethbridge, Alta. : University of Lethbridge, Faculty of Arts and Science, 2000, 2000)
vi, 103 leaves : ill. 28 cm. This paper purposes to answer some questions pertaining to perceptions of Metis identity (individual and collective, subjective and objective) as the Canadian public's conceptualizations of the Metis have been changed during the 80s and 90s by the works of Canadians historians and by popular media. These changes have been stimulated by the politics of Metis participation in: The Constitution Act, 1982; The First Ministers' Conferences [FM'Cs], 1983-1987; The Charlottetown Accord, 1992 Questions asked are (1) who are the modern-day Metis; (2) how do the Metis define themselves, conceptually and legally; (3) how does the Canadian public, in general, define the Metis? The results of the Lethbridge Area Metis Survey (Chapter Three) are valid for the local area but it is possible that they may be generalized.